Preoperative Information & informed consent in Patients undergoing Elective Surgery at Isra University Hospital, Hyderabad (Medical Forum Monthly, 2024)
Objective: The purpose of this study was to assess the patient’s awareness of informed consent and to evaluate the current practice of obtaining informed consent from patients proposed for elective surgery in tertiary care hospital.Study Design: Cross sectional surveyPlace and Duration of Study: This study was conducted in Isra University Hospital, Hyderabad, Sindh from 2nd April 2012 to 3rd March 2013.Materials and Methods: This study was designed as an observational investigation and no interference was made regarding the informed consent process to the patient. The selection criteria for the patients who were interviewed were convenience sampling. All adult patients of >18 years, who were undergoing various surgical procedures were interviewed after taking verbal informed consent on the second postoperative day, when they were comfortable to answer the questions. While all those patients who were uncomfortable due to pain or other reason and were unwilling to answer the questions were excluded from the study.All the patients were asked predesigned questions related to the information they were provided before the surgery as part of standard informed consent practice.Questions were asked in local language which includes the demographic data, operative details, risk, benefit, complications of surgery, type of anesthesia and alternative treatment options etc. The data was entered on SPSS version 16. Frequency & percentages were calculated to show the results.Results: Mean age of the patients was 34.95± SD 14.236 years. 220 patients were included in the study. 183(83.18%) patients were told about the indications of surgery while 136 (61.81%) patients were not told about any complication of Surgery. Type of anesthesia was discussed in only 25(11.36%) of patients while complications of anesthesia were discussed in only 18(8.18%) of patients. 165(75%) patients were not given time to ask the questions regarding their disease or surgery. Consent by the consultants was taken in only 63(28.63%) patients.Conclusion: The majority of the patients knew the indication of surgery but very few were informed about the possible complications and risk of the surgery and anesthesia..